2012
DOI: 10.1111/j.1600-6143.2012.04049.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Study to Assess the Conversion From Calcineurin-Inhibitors to Everolimus After Liver Transplantation—PROTECT

Abstract: Posttransplant immunosuppression with calcineurin inhibitors (CNIs) is associated with impaired renal function, while mTor inhibitors such as everolimus may provide a renal-sparing alternative. In this randomized 1-year study in patients with liver transplantation (LTx), we sought to assess the effects of everolimus on glomerular filtration rate (GFR) after conversion from CNIs compared to continued CNI treatment. Eligible study patients received basiliximab induction, CNI with/without corticosteroids for 4 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
202
2
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(221 citation statements)
references
References 19 publications
11
202
2
6
Order By: Relevance
“…In the H2304 study, patients did not receive induction therapy and MPA was not permitted after randomization. In contrast, the PROTECT study showed that patients given basiliximab induction with gradual early withdrawal of CNI (tacrolimus or cyclosporine [CsA]) over an eight-week period did not experience increased BPAR (10,11).…”
Section: Accepted Articlementioning
confidence: 89%
“…In the H2304 study, patients did not receive induction therapy and MPA was not permitted after randomization. In contrast, the PROTECT study showed that patients given basiliximab induction with gradual early withdrawal of CNI (tacrolimus or cyclosporine [CsA]) over an eight-week period did not experience increased BPAR (10,11).…”
Section: Accepted Articlementioning
confidence: 89%
“…In the PROTECT study, subjects were randomized to either conversion to everolimus-based immunosuppression or continuation of CNI-based therapy at 4 weeks after LTx (26).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, subsequent single-center observational studies (not clinical trials) comparing de novo sirolimus initiation at time of LTx have not shown an increased risk of graft failure or HAT as compared to other strategies, which underscore the importance of making the data of this multicenter study available to clinicians (15,20). Second, given emerging literature on the role of another mTOR inhibitor, everolimus, it is important to gauge whether similarities exist in the risk and benefit profile for these two medications (21)(22)(23)(24)(25)(26)(27). Above all, transparency in the full presentation of the results of the study are important given that it may impact our current approach to management of immunosuppression after LTx.…”
Section: Introductionmentioning
confidence: 99%
“…56,57,60 Two recently published studies have shown a better glomerular filtration rate in Everolimus group as compared to CNIs. 61,62 Metabolic Syndrome (MS)…”
Section: Kidney Injury and Immunosuppressionmentioning
confidence: 99%